Primary Osteosarcoma of the Breast Arising in an Intraductal Papilloma - Khalefa Ali Alghofaily; Musab Hamoud Almushayqih; Muhannad Faleh Alanazi; Abdullah Abdulrahman Bin Salamah; Halldor Benediktsson (Case Reports in Radiology)
Introduction. Primary osteosarcoma of the breast is extremely rare, and an osteosarcoma arising from an intraductal papilloma is exceptional. Case Presentation. A 72-year-old Saudi Arabian woman presented with a solid, bone-containing breast mass that was diagnosed as primary osteosarcoma of the breast on biopsy. She had a history of untreated intraductal papilloma. Treatment was completed with a modified mastectomy after excluding extramammary metastases. However, she subsequently developed multiple recurrent lesions at the same site. Conclusion. Primary osteogenic sarcomas of the breast are very rare. Although the main treatment is resection the optimal management remains uncertain and prognosis is poor.